2018
DOI: 10.1016/j.chest.2017.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Community-Acquired Pneumonia Visualized on CT Scans but Not Chest Radiographs

Abstract: Adults hospitalized with CAP who had radiological evidence of pneumonia on CT scan but not on concurrent chest radiograph had pathogens, disease severity, and outcomes similar to patients who had signs of pneumonia on chest radiography. These findings support using the same management principles for patients with CT-only pneumonia and those with pneumonia seen on chest radiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 31 publications
3
55
2
3
Order By: Relevance
“…In the present study, no abnormal findings suggestive of pneumonia were observed on CR in approximately 5% of hospitalized CAP patients, which was similar to the percentages (3–13%) in previous studies [1, 4, 7, 12]. The most common cause of negative CR findings in the present study was the location of the lesions in the dependent regions of the lungs, followed by GGO- or bronchiolitis-predominant pattern on CT and presence of lesions in the right middle lobe or lingula.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In the present study, no abnormal findings suggestive of pneumonia were observed on CR in approximately 5% of hospitalized CAP patients, which was similar to the percentages (3–13%) in previous studies [1, 4, 7, 12]. The most common cause of negative CR findings in the present study was the location of the lesions in the dependent regions of the lungs, followed by GGO- or bronchiolitis-predominant pattern on CT and presence of lesions in the right middle lobe or lingula.…”
Section: Discussionsupporting
confidence: 78%
“…A previous study also suggested that CAP patients with negative CR and positive CT findings exhibited a lower blood procalcitonin level than those with positive CR findings [12]. We speculate that lower blood levels of inflammatory markers are associated with more localized and less dense lesions in CAP patients with negative CR findings.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although the clinical significance of an infiltrate seen on CT but not on chest radiographs is debated, a recent prospective surveillance study showed that illness severity, pathogens, and clinical outcomes were comparable between patients with CAP with an abnormal chest radiographs and those diagnosed by CT scan without an obvious infiltrate on radiographs. 30 If clinical suspicion for pneumonia remains high despite a negative chest radiograph, advanced imaging should be considered and empiric treatment initiated. CT scans may be better at visualizing certain areas of the lung, such as the upper lobes and lingula, and at elucidating interstitial infiltrates as seen with atypical pathogens.…”
Section: Diagnosis: Imagingmentioning
confidence: 99%
“…The diagnosis is usually based on an abnormal chest radiograph (or increasingly lung ultrasound) in a patient with signs and symptoms of LRTI such as cough, fever, chest pain, sputum production, chills, sweats, and abnormal lung sounds . There are limited data regarding the accuracy of chest radiograph compared to a reference standard of chest computed tomography (CT), one study found sensitivity of 83% in a group of 280 patients with CAP confirmed by chest CT and another found a sensitivity of 90% in a group of 718 patients receiving both chest CT and chest X‐ray (CXR) . These studies were not able to calculate specificity.…”
mentioning
confidence: 99%